1986
DOI: 10.1007/bf00341761
|View full text |Cite
|
Sign up to set email alerts
|

An angiographic study of incidence and morphology of infundibular dilatation of the posterior communicating artery

Abstract: In the last 9 years, infundibular dilatation (ID) has been sought in 260 aneurysm (An) cases and 398 carotid angiogram's (CAG) to reveal its incidence and morphology. Findings were as follows: The incidence was about double that so far published. Small ID, usually triangular in shape, tended to become round as it grew larger (P less than 0.01). Large ID favored young age (P less than 0.05). In internal carotid-posterior communicating aneurysm (IC-P com An) cases, a high incidence of ID was noted as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…Therefore, a long period of follow up is necessary for patients with infundibular widening. More careful observation should be performed, especially in cases of infundibular widening 4) associated with a contralateral ICA-PcomA aneurysm, in young patients, in hypertensive patients, with well-developed PcomA, with a great divergent angle with respect to the ICA, or associated with a small bulge of the wall as in the present case.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, a long period of follow up is necessary for patients with infundibular widening. More careful observation should be performed, especially in cases of infundibular widening 4) associated with a contralateral ICA-PcomA aneurysm, in young patients, in hypertensive patients, with well-developed PcomA, with a great divergent angle with respect to the ICA, or associated with a small bulge of the wall as in the present case.…”
Section: Discussionmentioning
confidence: 72%
“…1,7,16) The occurrence and growth of infundibular widening seems to be influenced by the balance between the local tissue fragility of the infundibular wall and the hemodynamic stress. 4) Analysis of the intraoperative and angiographic findings of 34 lesions at the ICA-PcomA junction identified preoperatively as unruptured aneurysms because of a diameter exceeding 3 mm, non-visualized PcomA, or PcomA not originating at the apex of the widening found that six of the lesions were true aneurysms, four were enlarged infundibular widenings with reddish bulges (i.e., preaneurysmal bulge), and 24 were merely enlarged infundibular widenings without wall abnormality. 5) The diagnosis of cerebral aneurysm should not be based simply on the size and shape of the dilatation, especially if the PcomA does not fill or appears very small on carotid angiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…También se han considerado factores hemodinámicos relacionados con el efecto 'jet´1 4 . Ebina et al 6 estudiaron las características angiográficas de las DI y encontraron que una AComP bien desarrollada podría ser uno de los factores que puedan contribuir al desarrollo aneurismático a partir de una DI, en especial si ésta es grande o se asocia a un gran ángulo divergente entre la AComP y la ACI. La revisión de la bibliografía sugiere que existe una alta incidencia de buen llenado de la AComP en aneurismas desarrollados a partir de una DI.…”
Section: Aspectos Fisiopatológicosunclassified
“…El tiempo medio de progresión es de unos 7 años (rango, 0,5-11 años), aunque el tiempo de progresión viene determinado por la fecha de realización de la prueba de imagen y esto hace que los datos no representen con exactitud la realidad. Ebina et al 6 en un interesante trabajo elaboraron una serie de conclusiones con implicaciones pronósticas: que las pequeñas DI tienden a crecer, y en su crecimiento pasan de una forma triangular a una forma redondeada; que las DI más grandes aparecen en pacientes jóvenes; que hay un mayor número de casos de DI en pacientes que tienen un aneurisma de la AComP contralateral; que la HTA, al igual que tener una AComP bien desarrollada, son factores predisponentes para tener una gran DI y de forma redondeada además en el segundo caso; que aumenta la posibilidad de tener una DI de tamaño intermedio o grande a mayor ángulo de divergencia formado entre la ACI y la AComP; y, finalmente, los autores proponían para todos estos casos un exhaustivo control y/o tratamiento agresivo.…”
Section: Aspectos Fisiopatológicosunclassified